The Wannsee Conference on 20 January 1942: An introduction - Klein, Peter (Metropol Verlag, 2023)
On January 20, 1942, a meeting lasting one and a half hours took place in a villa at Wannsee. The only item on the agenda was the organization of the „Final Solution of the Jewish Question“. In fact, it was about a deportation and mass murder project with enormous dimensions, about which representatives of the security authorities and the ministries of the „Third Reich“ discussed with each other.The historian Peter Klein, a profound expert on the subject, gives a dense overview of the development that led to this conference and of the contents that were discussed there. He shows the significance of this coordination meeting and how its aftermath unfolded. Facsimiles of key documents on the „Wannsee Conference“ – including the minutes of the proceedings – make it possible to reconstruct the events from the fi les of the authorities involved and to grasp the specific character of this administrative murder of millions.